COVID-19 and Taxation : Between the Devil and the Deep Blue Sea - Junquera-Varela, Raul Felix; Alvarez Estrada, Daniel; Lucas-Mas, Cristian Oliver (World Bank, Washington, DC, 2021)
The objective of this working paper is to provide guidance on the dilemma that governments are facing because of the economic crisis triggered by COVID-19. Measures adopted by governments during the contention phase to alleviate cash flow pressures on taxpayers require budget expenditures that exacerbate revenue losses from reduced tax bases. In parallel, governments are struggling with public expenditure needs that call for creating fiscal space. During this crisis there has been a significant increase in digital transactions as well as an acceleration of digital economy business models and trends. As a result, new income sources have appeared, and governments must find ways of taxing them. The first part of this paper provides guidance on practical measures that may be applied by tax authorities to strengthen cash management and alleviate cash flow constraints on taxpayers. Most of these measures are applicable primarily during the contention phase of the COVID-19 health and economic crisis, but there are others well positioned to support the recovery phase. This paper elaborates on some of the recommendations profiled in the ‘Revenue Measurements on Tax and Customs’ document produced by the Fiscal Policy and Sustainable Growth unit,2 which serves as the umbrella document for this one. The main scope of this paper is to further develop specific practical measures for improving the cash management of businesses and households faced with liquidity constraints during this period. It also provides recommendations to revenue administrations for improving compliance and receipt monitoring during the contention phase. The second part of this paper focuses on post-crisis measures that may compensate for the fiscal deficit generated by cash flow management and temporary tax relief measures. This paper is a continuation, from a cash flow management perspective, of previous World Bank Group research conducted in the areas of fiscal policy and revenue administration implications in response to the COVID-19 pandemic.